Time evolution of composite fuel/water droplet radii before the start of puffing/micro-explosion; International Journal of Heat and Mass Transfer; Vol. 191 - Fedorenko R. M. Roman Mikhaylovich; Antonov D. V. Dmitry Vladimirovich; Strizhak P. A. Pavel Alexandrovich; Sazhin S. S. Sergey Stepanovich (2022, 2022)
Title screen